OC-013 The national early warning score (news) accurately discriminates the risk of serious in-hospital adverse outcomes in patients with liver disease. (17th June 2017) - Hydes, T; Meredith, P; Schmidt, P; Smith, G; Prytherch, D; Aspinall, R
Abstract : Introduction: Patients with liver disease who develop decompensation are at high risk of multiple organ dysfunction and death. The National Early Warning Score (NEWS), launched in the United Kingdom by the Royal College of Physicians, identifies adult inpatients at risk of deterioration. However, it includes physiological parameters that may be disturbed in cirrhosis, potentially reducing its accuracy. Therefore, we studied the performance of NEWS in acute and chronic liver diseases using a hospital dataset of over 3.5 million clinical observations. Method: In a major acute hospital serving a catchment of 650, 000, for all adult admissions between 2010 and 2014, the performance of NEWS was compared in patients: (i) assigned ICD-10 codes for primary and non-primary liver disease, and for patients without liver disease; (ii) assigned ICD-10 liver-related codes, subdivided clinically, e.g. acute (alcohol), acute (other), chronic non-cirrhotic and cirrhotic; and (iii) with liver disease grouped by Summary Hospital-level Mortality Indicator (SHMI) diagnoses for alcohol-related and other liver diseases. We compared the ability of NEWS and 34 other EWS to discriminate 24 hour mortality, cardiac arrest or unanticipated ICU admission using area under the receiver operating characteristics (AUROC) curve and by EWS efficiency curves. Results: During the study period 773 patients and 2525 patients were discharged with primary and non-primary diagnoses of liver disease. NEWS attained AUROC [CI] values of 0.873 [0.860–0.886], 0.898 [0.891–0.905] and 0.879 [0.877–0.881] for patients with primary, non-primary and no diagnoses of liver disease, respectively. Performance was significantly higher in patients with acute alcohol induced liver injury (AUROC [CI] 0.927 [0.912–0.941]) and although it was slightly lower in patients with cirrhosis, efficiency values remained relevant (AUROC [CI] 0.824 [0.797–0.850]). Similar results were seen for division by SHMI groups. NEWS outperformed all other EWS systems for patients with a primary or non-primary diagnosis of liver disease. Conclusion: NEWS accurately discriminates patients at risk of death, ICU admission or cardiac arrest within a 24 hour period for a range of liver-related diagnoses. Its widespread use provides a ready-made, easy-to-use option for identifying patients with liver disease who require early assessment and intervention, without the need to modify parameters, weightings or escalation criteria. Disclosure of Interest: None Declared